The leverage ratchet effect - Anat R. Admati; Peter M. DeMarzo; Martin Hellwig; Paul Pfleiderer (Max Planck Institute for Research on Collective Goods, 2013)
Shareholder-creditor conflicts can create leverage ratchet effects, resulting in inefficient capital structures. Once debt is in place, shareholders may inefficiently increase leverage but avoid reducing it no matter how beneficial leverage reduction might be to total firm value. We present conditions for an irrelevance result under which shareholders view asset sales, pure recapitalization and asset expansion with new equity as equally undesirable. We then analyze how seniority, asset heterogeneity, and asymmetric information affect shareholders choice of leverage-reduction method. Our results are particularly relevant to banking and highlight the benefit and importance of capital regulation to constrain inefficient excessive borrowing.
Keywords: 330